Perceived benefits, barriers and self-efficacy on health promoting behaviors among patients with type 2 diabetes mellitus at Khamthalesor Hospital - พรหมพันธ์ใจ พรพิชญ์; คัดทะเล ดวงรัตน์ (Disease Control Journal, 2014)
The purposes of this survey research were to determine the levels of perceived benefits, barriers and self-efficacy on health promoting behaviors, and to evaluate health promoting behaviors among patients with type 2 diabetes mellitus. The 799 populations were type 2 diabetes mellitus patients at Khamthalesor Hospital, Nakhonratchasima Province. Taro Yamane technique was applied for sample size (a = 0.05). Simple random sampling technique was used to recruit 269 samples. The perceived benefits, barriers and self-efficacy on health promoting behaviors among patients with type 2 diabetes mellitus questionnaire and the health promoting behaviors of type 2 diabetes mellitus patients questionnaire were used for data collection. Content validity indexes of these two questionnaires were 0.85 and 0.95, respectively. Cronbach’s alpha co-efficient for reliability of these two questionnaires were 0.85 and 0.95, respectively. Descriptive statistics was applied for data analysis. Results showed that the perceived benefit and barriers on health promoting behaviors among patients with type 2 diabetes mellitus were at moderate level (M = 2.33, SD = 0.87 and M = 2.50, SD = 0.82, respectively). The perceived self-efficacy on health promoting behaviors among patients with type 2 diabetes mellitus was at high level (M = 3.10, SD = 0.84). The health promoting behaviors of type 2 diabetes mellitus patients was at moderate level (M = 2.68, SD = 0.82). The personal information and levels of perceived benefits, barriers, and self-efficacy on health promoting behaviors included the level of health promoting behaviors of type 2 diabetes mellitus patients should be used as fundamental information when giving them suggestions and setting group activities on health promoting behaviors.